Foucault dan Teologi - Kebung, Konrad (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2020)
This article presents the relation between Michel Foucault’s philosophical thoughts and theology. So far one might hardly hear about the discussion of the impact of Foucault’s thought on theology and all disciplines related to it, such as religion, exegesis, spirituality, and the like. Recently many poststructuralists and postmodern thinkers have been interested in this issue. In fact, Foucault’s thoughts and analyses are considered very useful for the development of theology and the concepts of religious experience. Through his analyses of history and culture, Foucault prepares raw materials useful for theological reflections which are basically grounded on reality and the concrete life of humankind. Thus Foucault can help theology more rooted within reality, and therefore theology is not merely associated with the ecclesiological and dogmatic teachings of the Church, but can help them to be more easily digested and practised by the living community of the believers.